Evaluating the predictive character of the method of constrained geometries simulate external force with density functional theory - Wick, Christian; Topraksal, Ece; Smith, David M.; Smith, Ana-Suncana (Forces in Mechanics, 2022)
Mechanochemistry is a fast-developing field of interdisciplinary research with a growing number of applications. Therefore, many theoretical methods have been developed to quickly predict the outcome of mechanically induced reactions. Constrained geometries simulate External Force (CoGEF) is one of the earlier methods in this field. It is easily implemented and can be conducted with most DFT codes. However, recently, we observed totally different predictions for model systems of epoxy resins in different conformations and with different density functionals. To better understand the conformational and functional dependence in typical CoGEF calculations we present a systematic evaluation of the CoGEF method for different model systems covering homolytic and heterolytic bond cleavage reactions, electrocyclic ring opening reactions and scission of non-covalent interactions in hydrogen-bond complexes. From our calculations we observe that many mechanochemical descriptors strongly depend on the functional used, however, a systematic trend exists for the relative maximum Force. In general, we observe that the CoGEF procedure is forcing the system to high energetic regions on the molecular potential energy profiles, which can lead to unexpected and uncorrelated predictions of mechanochemical reactions. This is questioning the true predictive character of the method.
CRIS-Team Scopus Importer:2022-11-25
Keywords: COGEF; Density Functional Theory (DFT); Mechanical bond scission; Mechanical force; Mechanochemistry; Mechanoradicals; Molecular fracture

Mechanistic Insight into Solution-Based Atomic Layer Deposition of CuSCN Provided by In Situ and Ex Situ Methods - Hilpert, Felix; Liao, Pei-Chun; Franz, Evanie; Koch, Vanessa; Fromm, Lukas; Topraksal, Ece; Görling, Andreas; Smith, Ana-Suncana; Barr, Maissa; Bachmann, Julien; Brummel, Olaf; Libuda, Jörg (ACS Applied Materials and Interfaces, 2023)
Solution-based atomic layer deposition (sALD) processes enable the preparation of thin films on nanostructured surfaces while controlling the film thickness down to a monolayer and preserving the homogeneity of the film. In sALD, a similar operation principle as in gas-phase ALD is used, however, with a broader range of accessible materials and without requiring expensive vacuum equipment. In this work, a sALD process was developed to prepare CuSCN on a Si substrate using the precursors CuOAc and LiSCN. The film growth was studied by ex situ atomic force microscopy (AFM), analyzed by a neural network (NN) approach, ellipsometry, and a newly developed in situ infrared (IR) spectroscopy experiment in combination with density functional theory (DFT). In the self-limiting sALD process, CuSCN grows on top of an initially formed two-dimensional (2D) layer as three-dimensional spherical nanoparticles with an average size of ∼25 nm and a narrow particle size distribution. With increasing cycle number, the particle density increases and larger particles form via Ostwald ripening and coalescence. The film grows preferentially in the β-CuSCN phase. Additionally, a small fraction of the α-CuSCN phase and defect sites form.<br
Keywords: solution atomic layer deposition; liquid phase; in situ IR spectroscopy; atomic force microscopy; copper thiocyanate; neural network; density functional theory

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up